Virtual Learning Environment for Entrepreneurship: A Conceptual Model - Douglas Sparkes; Karin Schmidlin; Mark Hsu (Journal of Systemics, Cybernetics and Informatics, 2016)

(untitled)
The University of Waterloo has a history as an innovative and entrepreneurial university. With increasing demand for entrepreneurship education and venture development support there has been increasing interest in how to provide this support virtually. To address this need, an entrepreneurship platform consisting of four primary components; entrepreneurial team engagement, mentor engagement, provision of 'just-in-time' learning resources, and social network creation is under development. Engagement and social network creation are built around a series of gamified events that provide structure and feedback for the participants, as well as focal points for mentoring and network development. The 'embedding' of these early-stage ventures into a supportive social network aligns with a belief that one does not simply launch new ventures, but rather launch networks. These event gates are supported by a system of 'just-in-time' learning modules allow the participants to develop their own learning program, and may be drawn upon as needed. In this paper we discuss the conceptual model as well as progress on development of its key features. We also discuss some of the early results and lessons learned integrating it into several initiatives underway in Canada and Kenya.